Sealing glass powder with high chemical stability resistance and preparation method thereof

By preparing a high chemical stability sealing glass powder with a specific composition, the water resistance and chemical stability of the glass are improved by nitriding treatment, the problem of limited application of existing phosphate glass powder in the electronic packaging field is solved, and the effect of high thermal expansion coefficient and low sealing temperature is achieved.

CN119912168APending Publication Date: 2025-05-02CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510012717.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The application of existing phosphate glass powder in the electronic packaging field is limited by the problems of insufficient chemical stability and atmospheric corrosion resistance, and it is difficult to meet the needs of new electronic packaging fields for high expansion coefficient and high chemical stability.

Method used

By preparing a highly chemically stable sealing glass powder composed of Components I and Component II, Component I contains a specific proportion of oxides and Component II is a nitride, the water resistance and chemical stability of the glass are improved by nitriding treatment.

Benefits of technology

It achieves high thermal expansion coefficient, low softening point and high water resistance, meeting the requirements of high expansion coefficient and high chemical stability in the electronic packaging field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005228907660000061
    Figure BDA0005228907660000061
  • Figure BDA0005228907660000071
    Figure BDA0005228907660000071
Patent Text Reader

Abstract

The invention discloses sealing glass powder with high chemical stability resistance and a preparation method thereof, and belongs to the technical field of glass powder. The sealing glass powder is prepared from a component I and a component II; the component I is prepared from the following oxides: P2O5, Na2O, K2O, Li2O, CuO, Fe2O3, WO3, Al2O3, B2O3, BaO, SrO and MgO; and the component II is a nitride. The preparation method comprises the following steps: preparing a mixture according to the component I; crushing after melting; mixing the component I and the component II, and carrying out nitriding treatment; and crushing and grinding. The glass powder prepared by the method disclosed by the invention has low sealing temperature and high thermal expansion coefficient at the same time, and in addition, the glass powder is excellent in water resistance and reaches the standard of first-grade water resistance grade, so that the water resistance of the phosphate glass powder is remarkably enhanced, and the practical value and applicability of the phosphate sealing glass powder are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of glass powder, and in particular, relates to a sealing glass powder with high chemical resistance and stability and a preparation method thereof. Background Art

[0002] Low melting point sealing glass powder is an advanced welding material with low melting and sealing temperatures. It is widely used in many fields such as vacuum and microelectronics technology, laser and infrared technology, aerospace, etc., and realizes mutual sealing between glass, ceramics, metals, and semiconductors. At present, the low melting point sealing glass powder used in the market is mainly lead-containing glass powder, but as the EU has begun to enforce the "Directive on the Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment", environmental protection and lead-free have become the development direction of the world's electronics industry.

[0003] Phosphate glass powder is one of the important substitutes for traditional lead-containing glass powder. It has the advantages of lower glass transition temperature, suitable thermal expansion coefficient and lower viscosity, which makes phosphate glass of great value in the fields of electronic components. For example, Corning Company of the United States reported a P2O5-SnO2-ZnO glass in a patent, and also systematically studied the lead-free sealing glass of ZnO-SnO-P2O5 ternary system; Asahi Glass of Japan reported the P2O5-SnO2-ZnO-RO-R2O system; Japan Electronic Glass Company reported the P2O5-SnO2-B2O3 system glass. Although phosphate glass has many excellent properties, such as low melting temperature, controllable thermal expansion coefficient and other characteristics, which are required by many practical applications, the fatal weakness of this type of glass is its relatively poor chemical stability and resistance to atmospheric erosion, which severely limits its application in the field of electronic packaging and makes it difficult to meet the packaging requirements of high expansion coefficient and high chemical stability in the field of new electronic packaging. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a sealing glass powder with high chemical resistance and stability and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A sealing glass powder with high chemical resistance and stability, made of component I and component II;

[0007] The component I comprises the following oxides in molar percentages: P2O5: 40-60%, Na2O: 5-30%, K2O: 1-20%, Li2O: 0-10%, CuO: 10-40%, Fe2O3: 0-20%, WO3: 0-20%, Al2O3: 1-15%, B2O3: 1-15%, BaO: 0-10%, SrO: 0-10%, MgO: 0-10%;

[0008] The component II is a nitride.

[0009] Preferably, component I contains the following molar percentages of oxides P2O5: 45-55%, Na2O: 8-20%, K2O: 4-10%, Li2O: 0-5%, CuO: 20-30%, Fe2O3: 1-10%, WO3: 1-10%, Al2O3: 3-10%, B2O3: 3-10%, BaO: 1-5%, SrO: 0-5%, and MgO: 0-5%.

[0010] Preferably, the nitride is one of AlN, Si3N4 or Mg3N2, or a combination of two or more in any proportion.

[0011] Preferably, the total molar percentage content of Na2O+K2O+Li2O accounts for 15-25% of component I.

[0012] Preferably, the ratio of CuO / (CuO+Fe2O3+WO3) (the molar content of CuO accounts for the total molar content of CuO, Fe2O3 and WO3) is 85-95%.

[0013] Preferably, the mass ratio of the component I to the component II is 100:(5-15).

[0014] Another object of the present invention is to provide a method for preparing the above-mentioned glass powder, comprising the following steps:

[0015] (1) Preparing a mixed material: fully and uniformly mix the raw materials of component I in a mixer with zirconium balls added according to the proportion, and mix for 1 to 3 hours to prepare a mixed material;

[0016] (2) Melting: Place a crucible in a high-temperature electric furnace, add the mixture, raise the temperature to 900-1200°C according to a step temperature system, and keep it warm for 30-120 minutes to obtain a clear glass liquid;

[0017] (3) Crushing and grinding: The molten glass liquid is cooled by steel plate cooling or roller mill cooling, dried, and then ground by a ball mill, and passed through 50-mesh and 200-mesh sieves to obtain basic glass powder;

[0018] (4) weighing the base glass powder and component II in proportion, mixing them evenly in a three-dimensional mixing mixer, placing them in a graphite crucible, placing them in an atmosphere furnace, and heating them to 800 to 1000° C. to remelt the glass;

[0019] (5) When remelting begins, nitrogen is introduced to protect the sample. After reaching the melting temperature and keeping the temperature for 0.5 to 2 hours, the furnace temperature is lowered to 600 to 800°C and ammonia is introduced. The glass is nitrided under this condition for 2 to 24 hours, and then nitrogen is restored to protect the nitrided glass, and the furnace temperature is lowered to 400 to 500°C.

[0020] (6) taking out the glass block from the graphite crucible, annealing it in a dry annealing furnace at 350-400° C. for 2-6 hours, cooling it in the furnace, and grinding it to obtain a sealing glass powder with high chemical resistance and stability.

[0021] Preferably, the ammonia gas is introduced at a rate (flow rate per minute) of 0.6 to 1.2 times the furnace volume in step (5).

[0022] Both component II (nitride) and the introduction of ammonia can introduce N elements into the phosphate glass network structure, replacing O with three negative trivalent coupling bonds to form bulk P bonding with the glass network, significantly improving the cross-linking degree of the glass network, thereby improving the chemical stability of the phosphate glass; it should be added that simply introducing component II (nitride) can also achieve a certain amount of N incorporation, but the effect is limited, because the melting point of nitride is relatively high. If the amount used exceeds a certain range, the melting point of the finished glass powder will be increased, which is difficult to meet the applicable requirements; while the use of ammonia for nitriding treatment will introduce N elements and will not affect the melting point, but relying solely on ammonia treatment requires a nitriding time of up to several days, and the effect that can be achieved by the gas treatment method is also limited, and it is difficult to achieve the expected N doping; therefore, the combination of an appropriate amount of nitride and ammonia treatment with appropriate parameters can obtain the optimal expected nitriding treatment result.

[0023] Preferably, the water vapor content in the ammonia gas used in step (5) is ≤0.05%.

[0024] The thermal expansion coefficient of the sealing glass powder prepared by the above method at 300°C is greater than 170×10 -7 / ℃, expansion softening point<440℃, water resistance grade one.

[0025] The role of each glass component in the formula, the reasons for selecting the content, and the technical principles on which the present invention is based are:

[0026] P2O5 is a glass-forming oxide. It forms a structural network of phosphate glass with phosphorus-oxygen tetrahedron [PO4], but it will reduce the chemical stability of the glass. Pure phosphate glass is very easy to hydrolyze. The suitable range of P2O5 in the present invention is 40-60%. Alkali metal oxides Na2O, K2O, and Li2O do not participate in the network structure and belong to network external oxides. They play a role in increasing the thermal expansion coefficient of glass and reducing the softening temperature, but the chemical stability of the glass will be damaged. By adjusting the molar percentage of Na2O, K2O, and Li2O, using alkali metal ions Li + 、Na + , K + The radius difference forms a mixed alkali effect, which is beneficial to the melting of glass and the formation of glass state, and significantly improves the chemical stability of glass. In the present invention, the suitable range of Na2O is 5-30%, the suitable range of K2O is 1-20%, and the suitable range of Li2O is 0-10%.

[0027] Al2O3 is a glass network intermediate oxide, which can form aluminum oxide tetrahedron with double-bonded oxygen in phosphorus oxide glass, strengthen the phosphate glass structure, and can reduce the tendency of glass crystallization and improve a series of glass properties after introduction. However, if too much is introduced, the viscosity of the glass liquid will increase rapidly and melting will be difficult. The suitable range of Al2O3 in the present invention is 1-15%. B2O3 is a glass network generator oxide, which can improve a series of glass properties, such as reducing the thermal expansion coefficient and high-temperature viscosity of the glass, and can also play a good role in fluxing, accelerating glass melting and clarifying. However, too much use will cause glass phase separation or crystallization and reduce the chemical stability of the glass. The suitable range of B2O3 in the present invention is 1-15%.

[0028] The introduction of CuO, Fe2O3 and WO3 is beneficial to reduce the softening point of glass and improve the water resistance stability of phosphate glass. As a colorant, it can significantly improve the infrared spectrum absorption rate of the sealing glass, thereby reducing the sealing temperature. However, excessive introduction will lead to glass crystallization. In the present invention, the suitable range of CuO is 10-40%, the suitable range of Fe2O3 is 0-20%, and the suitable range of WO3 is 0-20%. Alkaline earth metal oxides BaO, SrO, and MgO do not participate in the network structure, belong to the network outside, and are beneficial to improve the stability of glass. Among them, BaO is beneficial to reduce the softening point of glass and improve the fluidity of glass in the low temperature zone, thereby reducing the sealing temperature of glass powder, and improving the production conditions and crystallization properties of glass, enhancing the hardness and corrosion resistance of glass. However, too high content of alkaline earth metal oxides will increase the tendency of glass crystallization. In the present invention, the suitable range of BaO is 0-10%, the suitable range of SrO is 0-10%, and the suitable range of MgO is 0-10.

[0029] Beneficial effects of the present invention:

[0030] 1. By adjusting the ratio of oxides such as P2O5, alkali metal oxides, CuO, Fe2O3, WO3, Al2O3, and BaO in the glass formula, a phosphate glass powder with a high thermal expansion coefficient and a low softening point is obtained; 2. The water resistance of the glass is significantly improved after nitridation treatment, which greatly expands the practical application range of phosphate sealing glass powder. In short, the glass powder prepared by the present invention has a high thermal expansion coefficient, a low sealing temperature, and high water resistance stability, which meets the requirements of the electronic packaging field for the chemical resistance stability of high expansion coefficient sealing glass powder. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] A method for preparing a sealing glass powder with high chemical resistance and stability, the specific steps are as follows:

[0033] (1) Preparing a mixed material: According to the formula shown in Table 1 below, the oxide components corresponding to the sealing glass powder in component I are converted into the introduced compound raw materials, and the raw materials are fully mixed in a mixer with zirconium balls added thereto for 2 hours to prepare a mixed material;

[0034] (2) Melting: Place the crucibles in a high-temperature electric furnace, add the mixed materials, raise the temperature to 1100°C according to the step temperature system, and keep it warm for 60 minutes to obtain clear glass liquid;

[0035] (3) Crushing and grinding: The molten glass liquid is cooled by a roller mill, dried, and ground by a ball mill, and passed through a 50-mesh and a 200-mesh sieve to obtain basic glass powder;

[0036] (4) accurately weighing the basic glass powder and component II nitride powder according to the designed ratio in Table 1, mixing them evenly in a three-dimensional mixing mixer, placing them in a graphite crucible, placing them in an atmosphere furnace, and heating them to 900° C. to remelt the glass;

[0037] (5) When remelting begins, nitrogen is introduced to protect the sample. After reaching the melting temperature and keeping the temperature for 1 hour, the furnace temperature is lowered to 700°C and then ammonia is introduced. The introduction rate (flow rate per minute) of ammonia is 0.8 to 1.0 times the furnace volume. The glass is nitrided under this condition for 6 hours, and then nitrogen is resumed to protect the nitrided glass, and the furnace temperature is lowered to 450°C.

[0038] (6) taking out the glass blocks from the graphite crucible, annealing a small portion of the glass blocks in a dry annealing furnace at 380° C. for 4 hours and then cooling the glass blocks in the annealing furnace for performance testing, and crushing and grinding the remaining glass blocks to obtain sealing glass powder with high chemical resistance and stability;

[0039] (7) Testing: The thermal expansion coefficient, expansion softening point, sealing temperature and water resistance stability of the glass powder are tested respectively. The thermal expansion coefficient and expansion softening point of the glass are tested in accordance with GB 16920-2015 "Determination of the average linear thermal expansion coefficient of glass", the sealing temperature is tested in accordance with GB / T 41742-2022 "Sealing glass for optoelectronic devices", and the water resistance stability is tested in accordance with GB / T6582-1997 "Test method and classification of particles of glass at 98°C for water resistance".

[0040] Table 1

[0041]

[0042]

[0043] Note: The values ​​shown in component I in Table 1 are molar percentages, which represent the molar percentage content of each component in component I; the values ​​shown in component II are mass percentages relative to the total amount of component I, and the amounts of component II and component I are in a one-to-one correspondence.

[0044] It can be seen from the data in the above table that the sealing glass powder prepared by the present invention has a thermal expansion coefficient of >170×10-7 / °C at 300°C, an expansion softening point of <440°C, and a water resistance grade of one; and combined with the data of the comparative example, it can be seen that the introduction of component II (nitride) and the introduction of ammonia for nitriding treatment can both improve the performance of the finished glass to a certain extent, but only the combination of the two can the best comprehensive performance be obtained.

[0045] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A sealing glass powder with high chemical resistance and stability, characterized in that: Made of component I and component II; The component I comprises the following oxides in molar percentages: P2O5: 40-60%, Na2O: 5-30%, K2O: 1-20%, Li2O: 0-10%, CuO: 10-40%, Fe2O3: 0-20%, WO3: 0-20%, Al2O3: 1-15%, B2O3: 1-15%, BaO: 0-10%, SrO: 0-10%, MgO: 0-10%; The component II is a nitride.

2. The sealing glass powder with high chemical resistance and stability according to claim 1, characterized in that: The component I contains the following oxides in molar percentages: P2O5: 45-55%, Na2O: 8-20%, K2O: 4-10%, Li2O: 0-5%, CuO: 20-30%, Fe2O3: 1-10%, WO3: 1-10%, Al2O3: 3-10%, B2O3: 3-10%, BaO: 1-5%, SrO: 0-5%, and MgO: 0-5%.

3. The sealing glass powder with high chemical resistance and stability according to claim 1 or 2, characterized in that: The total molar percentage content of Na2O, K2O and Li2O accounts for 15-25% of component I.

4. The sealing glass powder with high chemical resistance and stability according to claim 1 or 2, characterized in that: The molar content of CuO accounts for 85-95% of the total molar content of CuO, Fe2O3 and WO3.

5. The sealing glass powder with high chemical resistance and stability according to claim 1, characterized in that: The nitride is one of AlN, Si3N4 or Mg3N2, or a combination of two or more in any proportion.

6. The sealing glass powder with high chemical resistance and stability according to claim 1, characterized in that: The mass ratio of the component I to the component II is 100:(5-15).

7. The method for preparing a sealing glass powder with high chemical resistance and stability according to claim 1, characterized in that: The following steps are involved: (1) Preparing a mixed material: fully and uniformly mix the raw materials of component I in a mixer with zirconium balls added according to the proportion, and mix for 1 to 3 hours to prepare a mixed material; (2) Melting: Place a crucible in a high-temperature electric furnace, add the mixture, raise the temperature to 900-1200°C according to a step temperature system, and keep it warm for 30-120 minutes to obtain a clear glass liquid; (3) Crushing and grinding: The molten glass liquid is cooled by steel plate cooling or roller mill cooling, dried, and then ground by a ball mill, and passed through 50-mesh and 200-mesh sieves to obtain basic glass powder; (4) weighing the base glass powder and component II in proportion, mixing them evenly in a three-dimensional mixing mixer, putting them into a graphite crucible, placing them in an atmosphere furnace, and heating them to 800 to 1000° C. to remelt the glass; (5) When remelting begins, nitrogen is introduced to protect the sample. After reaching the melting temperature and keeping the temperature for 0.5 to 2 hours, the furnace temperature is lowered to 600 to 800°C and ammonia is introduced. The glass is nitrided under this condition for 2 to 24 hours, and then nitrogen is restored to protect the nitrided glass, and the furnace temperature is lowered to 400 to 500°C. (6) taking out the glass block from the graphite crucible, annealing it in a dry annealing furnace at 350-400° C. for 2-6 hours, cooling it in the furnace, and grinding it to obtain a sealing glass powder with high chemical resistance and stability.

8. The method for preparing a sealing glass powder with high chemical resistance and stability according to claim 7, characterized in that: In step (5), the ammonia gas is introduced at a rate (flow rate per minute) of 0.6 to 1.2 times the furnace volume.

9. The method for preparing a sealing glass powder with high chemical resistance and stability according to claim 7, characterized in that: The water vapor content in the ammonia gas used in step (5) is ≤0.05%.

Citation Information

Patent Citations

  • A kind of phosphate glass

    CN1285326A

  • Chemically durable nitrogen containing phosphate glasses useful for sealing to metals

    US4455384A

  • Fluorine-free phosphate glasses

    US5021366A

  • Alkali metal, copper phosphate glasses

    US5286683A

  • Cuprous metaphosphate glasses

    US5529960A